Does time varying risk premia exist in the international bond market? An empirical evidence from Australian and French bond market - Hira Aftab; Rabiul Alam Beg (International Journal of Financial Studies, 2021)
The presence of risk premium is an issue that weakens the rational expectation hypothesis. This paper investigates changing behavior of time varying risk premium for holding 10 year maturity bond using a bivariate VARMA-DBEKK-AGARCH-M model. The model allows for asymmetric risk premia, causality and co-volatility spillovers jointly in the global bond markets. Empirical results show significant asymmetric partial co-volatility spillovers and risk premium exist in the bond markets. The estimates of the bivariate risk premia show bi-directional causality exist between the Australia and France Bond markets. Overall results suggest nonexistence of pure rational expectation theory in the risk premium model. This information is useful for the agents' strategic policy decision making in global bond markets.
Keywords: C13; C18; C40; G1; 330; asymmetric volatility; bond market; partial co-volatility spillovers; risk premium